Evaluating the Effects of Entrepreneurial Orientation and Managerial Skills on Small and Medium Enterprises Performance in Lagos State - Nureni Sanusi Alaka; Obasuyi Okogua (The Winners, 2022)
The aim of the research was to examine the influence of entrepreneurial orientation and management skills on the performance of Small and Medium Enterprises (SMEs) in the state of Lagos, Nigeria. Quantitative survey research design was adopted, and multiple regression method of analysis was employed for the research. The population was 11.663 registered SMEs in Lagos State. Cochran's sample sizing was used to determine the sample size of 500. From the total of 500 questionnaires distributed, 473 were completed and returned, which corresponded to a response rate of 96,6%. The data collected were analyzed using both descriptive and inferential statistics. The results shows that entrepreneurial orientation practices have a positive and significant effect on profitability (β = 0,110, t = 1,904, p<0,05). However, management skills have a positive but not significant influence on the profitability of the selected SMEs (β = 0,030, t = 0,532, p>0,05). The research recommends that operators in this economic sector should look deeply at the variables of the research as essentials for improving business performance. It also put forward that Small and Medium business owners or managers should not be afraid of taking calculated risks as this would ensure their profitability.